Clostridium botulinum type C, D, C/D, and D/C: An update - Meurens, François; Carlin, Frédéric; Federighi, Michel; Filippitzi, Maria-Eleni; Fournier, Matthieu; Fravalo, Philippe; Ganière, Jean-Pierre; Grisot, Lionel; Guillier, Laurent; Hilaire, Didier; Kooh, Pauline; Le Bouquin-Leneveu, Sophie; et al. (Frontiers in Microbiology, 2023)
Clostridium botulinum is the main causative agent of botulism, a neurological disease encountered in humans as well as animals. Nine types of botulinum neurotoxins (BoNTs) have been described so far. Amongst these “toxinotypes”, the A, the B and E are the most frequently encountered in humans while the C, D, C/D and D/C are mostly affecting domestic and wild birds as well as cattle. In France for instance, many cases and outbreaks are reported in these animal species every year. However, underestimation is very likely at least for avifauna species where the detection of dead animals can be challenging. Knowledge about BoNTs C, D, C/D and D/C and the diseases they cause in animals and humans is still scarce and unclear. Specifically, the potential role of animal botulism outbreaks in cattle and poultry as a source of human illness needs to be further assessed. In this narrative review, we present the current knowledge about toxinotypes C, D, C/D and D/C in cattle and poultry with, amongst various other aspects, their epidemiological cycles. We also discuss the zoonotic potential of these toxinotypes and some possible ways of risk mitigation. An adapted and effective management of botulism outbreaks in livestock also requires a better understanding of these less common and known toxinotypes.